1998
DOI: 10.1002/biof.5520080124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen therapy on antioxidant status in newborns. Relationship with infection risk

Abstract: Newborns requiring intensive clinical care are susceptible to a wide range of excessive oxygen free radical production-related problems. In utero, fetal organs, particularly lungs, are exposed to relatively hypoxic tensions which rise abruptly after birth and this transition may cause oxidative injury in the neonate. The aims of this study were to determine oxygen free radical activity in neonates at the first 24 h, examine the role of immaturity and infection risk and compare the degree of oxidant stress in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Similarly, higher levels of selenium and other important antioxidants such as sulfhydryl groups have also been reported in newborn plasma (8,12). This suggests that the levels of some antioxidants are up-regulated in infants to compensate for increased oxidative stress at birth.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, higher levels of selenium and other important antioxidants such as sulfhydryl groups have also been reported in newborn plasma (8,12). This suggests that the levels of some antioxidants are up-regulated in infants to compensate for increased oxidative stress at birth.…”
mentioning
confidence: 79%
“…Other antioxidants, such as selenium and sulfhydryl groups, can be higher in infant plasma as well and contribute to its better protection against oxidation compared with adult plasma (8,12). In contrast, low levels of vitamin E (13) and carotenoids (14) observed in newborns seem to have no negative impact on plasma oxidative resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated a constant level of Sepp mRNA expression in the develop- ing lung and intestine at all embryonic stages. The fetal lungs are exposed to relatively hypoxic tensions which arise suddenly at birth, and this alternation may induce oxidative injury in neonates (Araujo et al, 1998). The diminution of Sepp expression in colon cancer may increase susceptibility to oxidative damage and tumor progression (Al-Taie et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that cGPx may act as an important antioxidant in limb and CNS development. Lungs are exposed to relatively high oxygen tensions, especially at birth, which causes oxidative injury in the neonate who is more susceptible to oxidative stress than in adult (Araujo et al 1998). Therefore, cGPx may act as a major protector against ROS massively produced by lung development.…”
Section: Discussionmentioning
confidence: 99%